Klasifikasi Naïve Bayes dan Confusion Matrix pada Pengguna Aplikasi E-Commerce di Play Store - Mohamad Rizki Humaidi; Alif Maulani (Jurnal Ilmiah Informatika, 2023)
Shopee is an e-commerce application that is very popular among Indonesians. Shopee is an online shopping service center that is in great demand by Indonesians and offers many types of products. In addition, the shopee application has features, one of which is shopee food and shopee pay, which distinguishes the shopee application from other e-commerce applications. Although there are many Shopee application users, of course not all reviews and ratings given by users are good as a reference for improving the Shopee application features. In conducting research, a method is needed that can classify review data into positive and negative reviews. One that provides a review and rating feature is the Play Store application. In this study, using 1528 review data, Positive and negative class labels are the categories used.. The machine learning classification method used is Naïve Bayes classification. The outcomes of the method's classification accuracy testing are measured using a confusion matrix. So that the accuracy result using Naïve Bayes classification is 0.87 or 87%. Based on these results, using the Naïve Bayes classification gets high accuracy results in the process of classifying review data on Shopee application user research in the Play Store.